A taxonomic revision of the afrotropical species of Selenops Latreille, 1819 (Araneae, Selenopidae) - Corronca, Jose Antonio (2002)
The Afrotropical species of the genus Selenops (Araneae, Selenopidae) are revised. Twenty-eight species are recognized and figured. The female of Selenops lumbo Corronca is described for the first time and eleven new species are described: Selenops angolaensis sp. nov. (female only) from Moçâdemes, Angola; S. ansieae sp. nov. (female only) from the Waterberg District, South Africa; S. cristis sp. nov. from Acara, S.W. Coast Africa (Namibia); S. dilamen sp. nov. (female only) from Tabora, Zaïre; S. dilon sp. nov. (female only) from Nelspruit, South Africa; S. feron sp. nov. (female only) from Baviaanspoort, South Africa; S. florenciae sp. nov. (female only) from Vilha Salazar, Angola; S. ilcuria sp. nov. (female only) from Marken, South Africa; S. lucibel sp. nov. from Kalahari; S. saldali sp. nov. (female only) from Achimota, Ghana and S. viron sp. nov. (female only) from Turkana, Kenya. Three species are listed as species inquirendae: S. fugitivus Walckenaer, 1837, S. modestellus Strand, 1907 and S. nanus Strand, 1907. S. ovambicus Lawrence, 1940 is here considered as a valid species. Lectotype and paralectotypes are designated for S. tenebrosus Lawrence, 1940 and S. krugeri Lawrence, 1940. Distribution data are given for all species and new data extend the ranges of some previously known species. A key to all recognized species is provided.